Cultivation of Character Values in Choukai Kaiwa Shokyu Kohan Course - Dwi Puji Asrini (Journal of Japanese Language Education and Linguistics, 2023)
Students who engage in the study of foreign languages may face the potential risk of experiencing a loss of their personal identity, as their sense of pride becomes intertwined with the cultural heritage of the country associated with the language they are acquiring. Students may also experience a decline in their sense of patriotism and attachment to their nation. Consequently, it is imperative to make concerted endeavors to incorporate character attributes within the curriculum provided. The present study employs a qualitative research approach that utilizes descriptive research methods. The individuals involved in this research were students enrolled in the Choukai Kaiwa Shokyu Kohan Course, which is a component of the Japanese Language Education Study Program. Data collection involved the utilization of many methods, including observation, interviews, documentation, and field notes. The character values have been derived from the Ministry of Education and Culture (2017). The data was analyzed to ascertain the character values that can be associated with the course themes and to classify the obstacles to fostering these character qualities. The Choukai Kaiwa Shokyu Kohan course offers the opportunity for the cultivation of several character traits, such as religiousness, honesty, discipline, industriousness, creativity, independence, curiosity, patriotism, sociability, and responsibility. The learning flow to teach character attributes consists of several steps: mite kangaeru (observe and think), miru-kiku-ittemiru (see, hear, ask, and experience), kiite kizuku (listen and notice), ruuru o hakensuru (analyze rules), tsukatte miru (practice and apply), Can Do chekku (check for proficiency), and seikatsu to bunka (life and culture).  One of the challenges encountered in cultivating character values is the limited capacity of teachers to assess all student groups during the process of integrating them into discussion exercises. Additionally, it is worth noting that only a subset of character values may be effectively evaluated through assignments.